Void distribution in a brazed cemented carbide steel joint analyzed by X-ray microscopy. (July 2019) - Yared, Wadih; Chen, Chih-Yu; Sievers, Norman; Tillmann, Wolfgang; Zielke, Reiner; Schimpfermann, Max
Highlights: X-ray CT reveals voids-distribution in the joint of a brazed sample. High resolution is possible for materials with similar absorption coefficients. Image reconstruction techniques offer accurate quantitative analysis of voids. Factors for a successful scan and dataset postprocessing are presented. Abstract: Brazing is a relatively fast process that offers sufficient strength in the joint of dissimilar materials. Cemented carbides are often brazed onto steel components in order to improve the wear resistance of engineering tools. In the case of brazing such materials in an ambient atmosphere, a flux is necessary to improve the wetting of the liquid filler alloy on the surfaces. In some cases, the flux cannot be sufficiently removed from the small joint, thus forming voids during solidification. This phenomenon can greatly affect the integrity of the joint. Such voids are not adequately detectable by visual inspection or common nondestructive testing methods, such as ultrasonic scanning, acoustic emission testing, or thermography. In this study, X-ray microscopy is shown to provide adequate visualization and a quantitative analysis of the dispersion of voids within brazed components of cold work steel, 115CrV3, and cemented carbide, K10 (ISO 513). One of the challenging tasks when analyzing the aforementioned brazed materials is achieving a sufficiently high resolution within the joint gap, since the sample materials have similar X-ray absorption coefficients. Such high resolution was successfully achieved in this study by means of multiple scanning and image reconstruction techniques, such as beam filtering, dataset levelling, and noise removal. The voids on the 115CrV3-side are found to expand radially towards the edges of the specimen up to a maximum volume of 1.18E + 07 µm 3 . The same radial pattern was detected on the side of the K10, where the voids contracted in volume towards the center of the specimen. However, the K10-side was found to exhibit relatively larger voids with a maximum volume of 7.70E + 07 µm 3, that is approximately seven times larger than that detected on the 115CrV3-side.